ANALISIS KEBERHASILAN USAHA MIKRO KECIL MENENGAH: Studi Kasus UMKM di Kecamatan Denpasar Utara - Ni Putu Lisa Ernawatiningsih; I Putu Edy Arizona (Universitas Triatma Mulya, 2022)
Usaha Mikro Kecil dan Menengah (UMKM) are an important part of the economy of a country or a region, including in Indonesia. The priority of national economic development in Indonesia is UMKM. The success of the business shows a situation that is better / superior than in the previous period. Three factors that affect the performance of small businesses, especially for new businesses according to the level of influence. These factors are industry structure, business strategy, and entrepreneurial characteristics. This study aims to determine the effect of entrepreneurial characteristics, business capital, marketing strategy, and self efficacy on business success in Usaha Mikro Kecil dan Menengah (UMKM) in North Denpasar District. The population of this study was 11,069 UMKM in the entire North Denpasar District. The sample calculation method was carried out using the slovin method with a sample of 100 UMKM. The sampling method is proportional random sampling method. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the characteristics of entrepreneurship, business capital, and marketing strategy have a positive effect on business success. Meanwhile, self efficacy have no effect on business success.